Yuhang Li, Becoming Guanyin: Artistic Devotion of Buddhist Women in Late Imperial China. Issue 2 (25th November 2022) - Mosher, Lucinda
Abstract : Yuhang Li, Becoming Guanyin: Artistic Devotion of Buddhist Women in Late Imperial China. New York: Columbia University Press (2020)